Iron Replacement Attenuates Hypoxic Pulmonary Hypertension by Remodeling Energy Metabolism via Regulating the HIF2α/Mitochondrial Complex I, III/ROS Axis - Yumei Geng; Huijie Wang; Zhenzhong Bai; Rili Ge (Biomolecules)
Iron deficiency is highly prevalent in patients with idiopathic pulmonary hypertension; nevertheless, its role and clinical significance in hypoxic pulmonary hypertension (HPH) remain elusive. Therefore, this study aims to clarify the role and molecular mechanisms of iron in HPH. By means of a retrospective analysis of clinical data from HPH patients and examinations of HPH animal models, we discovered that both HPH patients and animal models exhibit significant iron deficiency, characterized by reduced hepatic iron storage and elevated hepcidin expression. To further explore iron’s role in HPH, we modulated iron metabolism through pharmacological and dietary interventions in chronic hypoxic animal models. The results showed that iron deficiency exacerbated chronic hypoxia-induced pulmonary hypertension and right ventricular hypertrophy, while iron supplementation alleviated these conditions. Further investigations revealed that iron regulates HIF2α expression in pulmonary arterial endothelial cells (PAECs) under chronic hypoxia. Therefore, through in vivo and in vitro experiments, we demonstrated that HIF2α inhibition attenuates chronic hypoxia-induced pulmonary hypertension and right ventricular hypertrophy. Mechanistically, chronic hypoxia-mediated iron deficiency enhances HIF2α activation, subsequently suppressing iron/sulfur cluster assembly enzyme (ISCU) expression. This leads to decreased mitochondrial complexes I and III activity, increased reactive oxygen species (ROS) production, and inhibited oxidative phosphorylation. Consequently, metabolic reprogramming in PAECs results in a proliferation/apoptosis imbalance, ultimately exacerbating hypoxia-induced pulmonary hypertension and right ventricular hypertrophy. Collectively, our findings demonstrate that iron supplementation mitigates HPH progression by modulating HIF2α-mediated metabolic reprogramming in PAECs, revealing multiple therapeutic targets for HPH.